"Capillary‐Bridge Lithography" for Patterning Organic Crystals toward Mode‐Tunable Microlaser Arrays. Issue 1 (3rd November 2016) - Feng, Jiangang; Jiang, Xiangyu; Yan, Xiaoxu; Wu, Yuchen; Su, Bin; Fu, Hongbing; Yao, Jiannian; Jiang, Lei
Abstract : A versatile "capillary‐bridge lithography" technique is developed for patterning 1D organic single crystals and microring structures through controlling the generation and dewetting of capillary bridges on an interface with asymmetric wettability. High‐performance Fabry–Pérot and whispering‐gallery mode lasing emission with tunable modes are achieved on these 1D and microring structures.